Testing the Mediation Effect of Supervisor Ethical Leadership on the Relationship between Job Motivating Potential and Employee Pay Satisfaction and Job Satisfaction - Takach, Ali (2020)
Previous studies on the factors that influence employee pay satisfaction have highlighted the fact that all of the dimensions of organizational justice have a significant influence on employees’ attitudes and feelings regarding their pay. In spite of this, there is a lack of studies investigating the role of ethical leadership. The main objective of the present study was to investigate the mediation effect of supervisor ethical leadership on the relationships between job motivating potential and employee pay satisfaction. In addition, the study also aimed to investigate the relationship between overall job satisfaction and employee pay satisfaction. Based on a data gathered from a sample of 125 Lebanese employees through a web-survey, the study showed that there is a positive influence of job motivating potential on employee pay satisfaction. However, the mediation analysis revealed that supervisor ethical leadership does not mediate the relationship between job motivating potential and employee pay satisfaction. In addition, the study showed that overall job satisfaction has a positive influence on employee pay satisfaction. The results of the study are important since they bring significant contribution to the literature and the human resources management practice related to pay schemes and ethical leadership.